Faktor Budaya dalam Pemasaran Produk UMKM di Kecamatan Sukahening - Arhasy, Aneu Nurkhalifah Arhasy; Romdoni, Muhammad Luthfi Romdoni (ICON Publisher, 2025)
This study investigates the role of cultural factors in shaping the marketing effectiveness of micro, small, and medium enterprises (MSMEs) in Sukahening District, Indonesia. Employing a qualitative methodology grounded in Hofstede’s Cultural Dimensions Theory, the research collected data through in-depth interviews, observations, and thematic analysis. Findings reveal that collectivism, local linguistic preferences, and traditional semiotics profoundly influence consumer trust, brand recall, and purchasing decisions. MSMEs that actively incorporated local languages, cultural symbols, and engaged community elders experienced stronger market penetration and loyalty compared to those adopting generic strategies. Conversely, neglecting cultural integration led to weakened consumer connections and limited word-of-mouth diffusion. The study underscores the necessity of culturally embedded marketing as a strategic asset rather than a peripheral consideration. It further suggests that policymakers and local institutions could enhance MSME competitiveness by promoting cultural marketing literacy and support schemes. This research enriches both theoretical perspectives on culture-consumer relationships and offers practical pathways for MSMEs to leverage cultural authenticity for sustainable growth in culturally cohesive regions.